Innate defense regulator peptide 1018 protects against perinatal brain injury. Issue 3 (7th March 2014) - Bolouri, Hayde; Sävman, Karin; Wang, Wei; Thomas, Anitha; Maurer, Norbert; Dullaghan, Edie; Fjell, Christopher D.; Ek, C. Joakim; Hagberg, Henrik; Hancock, Robert E. W.; Brown, Kelly L.; Mallard, Carina
<x xml:space="preserve">Abstract</x> Objective There is currently no pharmacological treatment that provides protection against brain injury in neonates. It is known that activation of an innate immune response is a key, contributing factor in perinatal brain injury; therefore, the neuroprotective therapeutic potential of innate defense regulator peptides (IDRs) was investigated. Methods The anti‐inflammatory effects of 3 IDRs was measured in lipopolysaccharide (LPS)‐activated murine microglia. IDRs were then assessed for their ability to confer neuroprotection in vivo when given 3 hours after neonatal brain injury in a clinically relevant model that combines an inflammatory challenge (LPS) with hypoxia–ischemia (HI). To gain insight into peptide‐mediated effects on LPS‐induced inflammation and neuroprotective mechanisms, global cerebral gene expression patterns were analyzed in pups that were treated with IDR‐1018 either 4 hours before LPS or 3 hours after LPS+HI. Results IDR‐1018 reduced inflammatory mediators produced by LPS‐stimulated microglia cells in vitro and modulated LPS‐induced neuroinflammation in vivo. When administered 3 hours after LPS+HI, IDR‐1018 exerted effects on regulatory molecules of apoptotic (for, eg, Fadd and Tnfsf9) and inflammatory (for, eg, interleukin 1, tumor necrosis factor α, chemokines, and cell adhesion molecules) pathways and showed marked protection of both white and gray brain matter. Interpretation IDR‐1018 suppresses proinflammatory mediators and cell injurious mechanisms in the developing brain, and postinsult treatment is efficacious in reducing LPS‐induced hypoxic–ischemic brain damage. IDR‐1018 is effective in the brain when given systemically, confers neuroprotection of both gray and white matter, and lacks significant effects on the brain under normal conditions. Thus, this peptide provides the features of a promising neuroprotective agent in newborns with brain injury. ANN NEUROL 2014;75:395–410